Aneuploidy and chromosomal instability in cancer : a jackpot to chaos - Giam, Maybelline (2015)
Genomic instability (GIN) is a hallmark of cancer cells that facilitates the acquisition of mutations conferring aggressive or drug-resistant phenotypes during cancer evolution. Chromosomal instability (CIN) is a form of GIN that involves frequent cytogenetic changes leading to changes in chromosome copy number (aneuploidy). While both CIN and aneuploidy are common characteristics of cancer cells, their roles in tumor initiation and progression are unclear. On the one hand, CIN and aneuploidy are known to provide genetic variation to allow cells to adapt in changing environments such as nutrient fluctuations and hypoxia. Patients with constitutive aneuploidies are more susceptible to certain types of cancers, suggesting that changes in chromosome copy number could positively contribute to cancer evolution. On the other hand, chromosomal imbalances have been observed to have detrimental effects on cellular fitness and might trigger cell cycle arrest or apoptosis. Furthermore, mouse models for CIN have led to conflicting results. Taken together these findings suggest that the relationship between CIN, aneuploidy and cancer is more complex than what was previously anticipated. Here we review what is known about this complex ménage à trois, discuss recent evidence suggesting that aneuploidy, CIN and GIN together promote a vicious cycle of genome chaos. Lastly, we propose a working hypothesis to reconcile the conflicting observations regarding the role of aneuploidy and CIN in tumorigenesis.